Diversifikasi Produk Lada Hitam (Piper nigrum L.) Sebagai Obat Herbal Tuberkulosis Paru - Ismail; Rahmatia, Sitti; Basri, Muhammad; Sukriyadi; Supu, Junaidi; Baharuddin, Baharuddin (Bhakti Persada Jurnal Aplikasi IPTEKS, 2025)
Background: Pulmonary tuberculosis (PTB) remains a global health challenge, especially with the increasing drug resistance of Mycobacterium tuberculosis. Piper nigrum L. and its bioactive compound, piperine, have shown potential as antimicrobials and immunomodulatory agents. Objective: This study aimed to evaluate the potential of Piper nigrum and its active compound, piperine, as adjunctive therapy for pulmonary tuberculosis (PTB). Methods: The study utilized a mixed-methods design with 50 participants diagnosed with PTB. The treatment group received Piper nigrum L. extract supplementation at varying doses (low, medium, high) for eight weeks. Quantitative data were collected through measurement of bacterial load and immune response, while qualitative data were obtained through semi-structured interviews. Statistical analysis was conducted using SPSS software, involving paired t-tests and regression analysis to explore dose-response relationships. Results: showed significant improvement in symptom reduction and immune response in the treatment group compared to the control group. At week 8, the treatment group exhibited a 70% reduction in symptoms and a 60% increase in immune.  A dose-response effect was evident, where a high dose of piperine resulted in a 75% reduction in bacterial load and a 65% increase in immune response.  Conclusion:  Piper nigrum L. has great potential as an adjunctive therapy for PTB by enhancing the effectiveness of conventional treatment.